Как узнать любовь?: повесть / И. Молчанова - Мазаева Ирина (Только для девчонок, 2011)
Экземпляры: аб. (20191008) / Инвентарный номер: 59801 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44